Dakwah Pencerahan di Ruang Mitigasi Penyintas Gempa Sulawesi Barat - Muhammad Alifuddin,; Suarni,; Risman Iye, (Jurnal Komunikasi Islam, 2022)
This study aims to describe "da'wah pencerahan” (enlightening proselytism) in the mitigation sphere of the West Sulawesi earthquake survivors, conducted by the Muhammadiyah Disaster Management Center (MDMC). This research is a qualitative study using a phenomenological approach. The research findings state that, first, the enlightening da'wah is carried out through a number of socio-cultural activities that are oriented toward building logical thoughts and positive attitudes for survivors in responding to disasters. Second, the enlightening da'wah is carried out through three methods, namely da'wah bi al-lisan or verbal socialisation in public places and in places of worship; da'wah bi al-kitabah conducted through written messages via brochures and social media; da'wah bi al-hal (bi al-a'mal) which is carried out through measurable and planned actions. Third, the enlightenment da'wah movement of MDMC is open, inclusive, and universal for humanity.